2021
DOI: 10.1021/acsami.0c20352
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Interfacial Properties of Fluorous Colloids Toward Ultrasound Programmable Bioactivity

Abstract: Liquid-in-liquid emulsions are kinetically stable colloids that undergo liquid-to-gas phase transitions in response to thermal or acoustic stimuli. Perfluorocarbons (PFCs) are preferred species as their highly fluorinated nature imparts unique properties that are unparalleled by nonfluorinated counterparts. However, traditional methods to prepare PFC emulsions lack the ability to precisely tune the thermodynamic stability of the fluorous−water interphase and consequently control their vaporization behavior. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…[ 23 ] This assertion is based on our prior observations that assembly of fluorinated small molecules at the surfaces of PFC liquids alters the surface tension, decoupled from droplet size, to precisely control the US vaporization of uniform dimension emulsions. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 23 ] This assertion is based on our prior observations that assembly of fluorinated small molecules at the surfaces of PFC liquids alters the surface tension, decoupled from droplet size, to precisely control the US vaporization of uniform dimension emulsions. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…Insights explaining this behavior can be gleaned from our prior work with small molecule perfluoroalkyl emulsifiers. [ 24 ] Here, an optimal fluoroalkyl tail length for perfluorocarboxy amphiphiles was identified that favored their preferential assembly at fluorous–water interfaces, rather than solubilization by either bulk solvent. Relating this to the current study suggests that the RGD‐3F F peptide possesses a unique counterbalance of polarity and fluorine content that is ideally suited for assembly at PFC–water interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work from our lab has shown that non‐canonical amino acids can be directed to assemble at fluorous‐water interfaces to develop mechanically responsive thin films and viscoelastic synthetic mucus (Miller & Medina, 2024; Sloand, Culp, et al, 2021; Sloand, Rokni, et al, 2021). Mechanistic insights gained from this work enabled the development of fluorine‐rich small molecules and peptides that act as emulsifiers to stabilize perfluorocarbon nanodroplets (Kim et al, 2023; Lawanprasert et al, 2021; Medina et al, 2017; Sloand et al, 2020; Sloand, Culp, et al, 2021; Sloand, Rokni, et al, 2021). By controlling the physicochemical properties of the emulsifier, we have shown that the thermodynamic stability of phase separated emulsions can be rationally tailored to enable thermally and mechanically responsive nanomaterials.…”
Section: Interface‐driven Assembly Mechanismsmentioning
confidence: 99%
“…The stabilising shell is directly involved in the bonding with the carried agents (e.g., drugs or functional nanoparticles) and in the targeting towards specific tissues [16,17], it could affect the vaporisation efficiency, and it determines the acoustic response of the MBs formed after vaporisation [18][19][20][21]. On top of these, the primary role of the shell lies in ensuring the stability and the size uniformity of MDs over time.…”
Section: Introductionmentioning
confidence: 99%